Determination of Vitamin C Levels in Red Apples ( Malus domestica ) and Green Apples ( Malus silvestris ) Using The Iodimetric Method - Febrina; Ratih Nurwanti; Yayuk Sri Rahayu (International Journal of Multidisciplinary Learners, 2025)
Apple is one of the best types of fruit and is very much liked by people because of its different taste and rich nutritional and vitamin content, especially vitamin C. This study aims to determine the level of vitamin C in red apples (Malus domestica) and green apples (Malus silvestris). One of the chemicals that has many benefits for human health is vitamin C. This is a laboratory experiment using iodimetry, which is a direct titration process between iodine and vitamin C. The results of the I2 standardization test showed an I2 concentration of 0.0652 N. For testing vitamin C levels, the average value at the end of the titration for red apples (Malus domestica) was 27.54048 mg and for green apples (Malus silvestris) was 45.9008 mg. Therefore, it can be concluded that green apples (Malus silvestris) have higher levels of vitamin C than red apples (Malus domestica).